Profil Keterampilan Berpikir Kreatif Peserta Didik SMK - Meiarti, Devi (Universitas Nurul Huda, 2021)
The aim of this research is to analyze the initial profile of creative thinking skills in Vocational School students on physics learning. This research was a quantitative descriptive research using test method. The population used in this study were all students of class XII at SMK Islam Nurul Hadi in Demak Regency. The sample used was 30 student’s selected by random sampling. The instrument used is a open-ended test with four items each representing an indicator of creative thinking. The indicators used are indicators that had been developed by an expert. The result of students’ creative thinking skills in physic subject showed 56,67% which was categorized as sufficient. It was shown from the creative thinking skills indicators that fluency 61,11%, flexibility and originality 57,78%, and elaboration 50,00%. Overall, it could be concluded and said that the ability of student’s creative thinking had not been properly trained. However, for fluency indicator were eventually considered well-trained.